Character association and path co-efficient analysis in wheat (Triticum aestivum L.) (Bangladesh Journal of Agricultural Research, 2017)
The experiment was carried out with 50 wheat lines to study their mean, range, cv (%), correlation co- efficient, and path co- efficient considering 14 different morphological characters at the experimental field of Regional Wheat Research Centre (RWRC), Bangladesh Agricultural Research Institute (BARI), Gazipur during December 2010 to April 2011. Significant variation was observed among the genotypes for all characters studied. In general, genotypic correlations were higher than the phenotypic correlations. It indicates that there was an inherent association among them which was adversely influenced by the environment. The correlation coefficients showed that, seed yield was negatively and significantly correlated with days to heading (DTH), plant height (PHT), days to anthesis (DTA), days to physiological maturity (DPM), and canopy temperature at anthesis stage (CTanth.) but only negatively correlated with canopy temperature at vegetative stage (CTveg.), canopy temperature at grain filling stage (CTgf.), spikelets per spike both genotypically and phenotypically and grain per spike showed genotypically negative correlation. Path analysis showed that plant height (PHT), days to physiological maturity (DPM), canopy temperature at grain filling stage (CTgf.), and thousand grain weight (TGW) influenced seed yield directly in positive direction but days to heading (DTH), days to anthesis (DTA), grain filling duration (GFD), grain filling rate (GFR), Chlorophyll content at anthesis stage (CHLA), canopy temperature at vegetative stage (CTveg.), canopy temperature at anthesis stage (CTanth.), spikelets per spike, and grains per spike had negative direct effect on seed yield. Considering analytical findings of correlation co-efficient, path co-efficient analysis and field performance, the genotypes G 3, G 10, G 11, G 12, G13, G 21, G 29, G 35, G 38, G 40, G 46 and G 48 were found suitable for future breeding programme.Bangladesh J. Agril. Res. 42(3): 571-588, September 2017